Prosiding Seminar IRPA RMK-7 - Seminar IRPA RMK-7 (2000 : Malacca, Malaysia).; Ismail Sahid; Roslan Abd. Shukor; Universiti Kebangsaan Malaysia. Pusat Pengurusan Penyelidikan; Malaysia. Kementerian Sains, Teknologi dan Alam Sekitar. Intensification of Research in Priority Areas (Bangi, Selangor : Pusat Pengurusan Penyelidikan, Universiti Kebangsaan Malaysia, 2000)
Research on agricultural industries, social science, technology, etc. in Malaysia; papers of a seminar.
Koleksi Sumbangan : Prof. Datuk (Dr.) Anuwar Ali
Includes bibliographical references.
Keywords: Universiti Kebangsaan Malaysia -- Research -- Congresses; Universities and colleges -- Research -- Malaysia -- Research -- Congresses